Pengaruh Kualitas Pelayanan dan Kepuasan Wisatawan Terhadap Perilaku Pasca Berkunjung Ke Desa Wisata Kuta Kabupaten Lombok Tengah yang Dimediasi Budaya Lokal - Cahyaditya, Ryandha; Permadi, Lalu Adi (Universitas Mataram, 2024)
This research aims to determine the influence of Service Quality and Tourists Satisfaction on Post-Visit Behavior in the Kuta Tourism Village, Central Lombok Regency, mediated by Local Culture. The population studied comprises individuals who have visited the Kuta Tourism Village at least once, and the sample consists of 100 respondents selected using purposive sampling techniques. This study utilized the Structural Equation Modeling-Partial Least Square (SEM-PLS) data analysis method with the assistance of Smart-PLS version 4.0 software. The research findings indicate that Service Quality does not have a significant influence on either Post-Visit Behavior or Local Culture. On the other hand, Tourists Satisfaction has a significant influence on both Post-Visit Behavior and Local Culture. Lastly, Local Culture significantly influences Post-Visit Behavior. However, the Local Culture variable is unable to mediate between the Service Quality and Tourists Satisfaction variables concerning Post-Visit Behavior